Come Now, Let Us Reason Together: Cognitive Bias, Individualism, and Interactionism in Critical Thinking Education - Dacey, Austin (Informal Logic, 2020)
In defending a new framework for incorporating metacognitive debiasing strategies into critical thinking education, Jeffrey Maynes (2015; 2017) draws on ecological rationality theory to argue that in felicitous environments, agents will achieve greater epistemic success by relying on heuristics rather than more ideally rational procedures. He considers a challenge presented by Mercier and Sperber’s (2011; 2017) “interactionist” thesis that individual biases contribute to successful group reasoning. I argue that the challenge can be met without assuming an individualist ideal of the critical thinker as a solitary reasoner. Focusing on cognitive laziness and myside bias, I then argue that a more complete reckoning with the implications of interactionism about reasoning will require us to transcend individualism more fully to embrace the selection, design, regulation, and navigation of dialogic environments as central pedagogical aims of critical thinking education.